2016
DOI: 10.1088/1751-8113/49/50/505001
|View full text |Cite
|
Sign up to set email alerts
|

The probability density function tail of the Kardar–Parisi–Zhang equation in the strongly non-linear regime

Abstract: An analytical derivation of the probability density function (PDF) tail describing the strongly correlated interface growth governed by the nonlinear Kardar-Parisi-Zhang equation is provided.The PDF tail exactly coincides with a Tracy-Widom distribution i.e. a PDF tail proportional to2 ), where w 2 is the the width of the interface. The PDF tail is computed by the instanton method in the strongly non-linear regime within the Martin-Siggia-Rose framework using a careful treatment of the non-linear interactions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…The scaling limits in higher dimensions are controversial issues even in physics and there are some candidates. See [3] and references therein. However, Zhang showed that if τ obeys the Bernoulli distribution, the shape fluctuation diverges [17].…”
Section: Introductionmentioning
confidence: 99%
“…The scaling limits in higher dimensions are controversial issues even in physics and there are some candidates. See [3] and references therein. However, Zhang showed that if τ obeys the Bernoulli distribution, the shape fluctuation diverges [17].…”
Section: Introductionmentioning
confidence: 99%